The Impact of Servant Leadership on Operational Excellence: Case from Public Sector of Jordan - edwan, Shaker; K. Al-Batayneh, Hisham (Jordan Journal of Business Administration, 2025)
This paper aims to explore the impact of servant leadership in its five dimensions (putting subordinates first, helping subordinates grow and succeed, creating value for society, empowerment and humility) on operational excellence in the Jordanian public sector. The quantitative approach was used to achieve the study objectives. More specifically, a questionnaire was developed and distributed to (331) employees at seven public sector institutions. The study reached a number of findings, the most important of which are: 1) There is a moderate level of practicing servant leadership behaviors by leaders in the Jordanian public sector. 2) There is a high level of operational excellence practices in the Jordanian public sector. 3). There is a statistical positive impact of “creating value for society” and humility as pillars of servant leadership on operational excellence. 4) There is no statistically significant effect for “helping subordinates to grow and succeed” and “empowerment” on operational excellence in the Jordanian public sector. Lastly, this paper provided several recommendations including enhancing practices related to the dimensions of creating value for society and humility in the servant leadership style and in other leadership styles in public sector institutions to achieve sustainable operational excellence, and training government leaders on the servant leadership style because of its positive effects on operational excellence